2020
DOI: 10.1155/2020/9185361
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Protective Effect of Cimetidine and Verapamil on Paracetamol-Induced Hepatotoxicity in Mice

Abstract: Paracetamol, chemically known as acetaminophen, if taken in higher doses has hepatotoxic potential. Cimetidine by inhibiting the cytochromal enzymes and reducing the production of the toxic metabolite can reduce the hepatotoxic potential while Verapamil can act as a hepatoprotective by maintaining calcium homeostasis. The present study was conducted to study the hepatoprotective activity of Cimetidine and Verapamil against the toxicity induced by paracetamol. In addition to the group receiving only distilled w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…There were no significant changes in blood biochemical parameters, including alanine transaminase (ALT), aspartate transaminase (AST), lactic dehydrogenase (LDH), creatinine (CREA), and uric acid (UA), as well as hematoxylin and eosin (H&E) staining images of main organs, including the heart, liver, spleen, lung, and kidney (Figure A–C). However, ALT and AST, as well as liver function markers, were significantly higher in the blood of 10 -treated nude mice (300 mg/kg), indicating the hepatic injury . Amazingly, compared with the control group, H&E of liver tissues did not show significant changes in the 10 -treated group (25 mg/kg).…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…There were no significant changes in blood biochemical parameters, including alanine transaminase (ALT), aspartate transaminase (AST), lactic dehydrogenase (LDH), creatinine (CREA), and uric acid (UA), as well as hematoxylin and eosin (H&E) staining images of main organs, including the heart, liver, spleen, lung, and kidney (Figure A–C). However, ALT and AST, as well as liver function markers, were significantly higher in the blood of 10 -treated nude mice (300 mg/kg), indicating the hepatic injury . Amazingly, compared with the control group, H&E of liver tissues did not show significant changes in the 10 -treated group (25 mg/kg).…”
Section: Resultsmentioning
confidence: 85%
“…However, ALT and AST, as well as liver function markers, were significantly higher in the blood of 10-treated nude mice (300 mg/kg), indicating the hepatic injury. 48 Amazingly, compared with the control group, H&E of liver tissues did not show significant changes in the 10-treated group (25 mg/kg). The results suggested that a low dose (25 mg/kg) of compound 10 was safe for biomedical application without serious toxicity and adverse events, while high dosages (300 mg/kg) were toxic.…”
Section: Compound 38k Exerts Antimigration and Antiproliferative Acti...mentioning
confidence: 81%